2020
DOI: 10.2217/fon-2020-0585
|View full text |Cite
|
Sign up to set email alerts
|

Radiology Management of a ‘Breast Unit’ During COVID-19 Pandemic: a Single Institution Experience

Abstract: Aim: To describe the activity in the ‘breast unit’ at the department of radiology during the coronavirus disease 19 lockdown in a university hospital treating coronovirus disease 19 patients in a Middle-Eastern developing country. Materials: This was a retrospective study conducted from March 9 until 11 May 2020, in the breast unit at the department of radiology of a central university hospital in a Middle-Eastern developing country. Data were collected from 205 patients visiting the breast unit during the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…Salem et al performed a retrospective study at a breast imaging unit at a university hospital from March to May 2020 and reported that there was a 73% reduction in overall breast unit activity comprising mammograms, MRIs and ultrasounds. Screenings and BCa surveillance were two of the indications for mammogram and it was noted that radiology staff made significant adjusts in ensuring continued quality care whilst maintaining patients' safety [32]. In another study which conducted a risk assessment of the use of three BCa services including breast surgery and breast imaging in February-April 2020, there was significant decrease in breast imaging with a mean weekly reduction of 61.7% [33].…”
Section: Telehealth Covid-19 and Breast Cancer Screeningmentioning
confidence: 99%
“…It should also be kept in mind that almost all the studies carried out considered the natural history of disease in diagnosis and treatment. After the outbreak of the Covid-19, studies have been conducted on the changes in the course of the disease and the delay in the diagnosis and treatment of breast cancer, which has also affected the indirect costs of the disease [ 70 72 ].…”
Section: Discussionmentioning
confidence: 99%